III World Social Forum (Journal of Parents and Teachers, 2014)
The Global Forum is a space for debate that allows us to reflect, formulate proposals and exchange experiences with networks, governmental and non-governmental organizations that oppose neoliberal globalization and the domination of capital. In particular this year's FM has addressed five thematic axes, such as: political power, civil society and democracy.
Keywords: debate; Brazil; democracy; human rights; culture; politics